Pedagogy and Psychology as Sciences for the Formation of the Potential of Modern Society - Nikolina V. V., Aksenov S. I., Zulkharnaeva A. V., Loshchilova A. A., Fefelova O. E., Frolova S. V., Koniushenko S. M., Komissarova M. O., Smykovskaia T. K., Petrova T. M., Plashchevaia E. V., Utochkina E. A., Prozorova M. N., Arefeva S. A., Arefeva O. V., Selivanova M. E., Pokhilko A. D., Kazachenko O. A., Zanin D. S., Golubeva M. M., Moiseeva K. S., Sudakov O. V., Sudakov D. V., Gordeeva O. I., Sych G. V., Rusina E. V., Kniazeva E. G., Akhmadeeva E. V., Biriukova I. A., Miriutsa E. V., Polushkina I. V., Topilskaia O. A., Iureva T. V., Uvarov E. A. (Pedagogy and Psychology as Sciences for the Formation of the Potential of Modern Society, 2024)
the study is designed to identify the relationship between self-presentation strategies and personality orientation in communication in adolescence. Self-presentation is understood as the totality of all human actions aimed at creating a certain image in the eyes of the audience, which can be either an individual or a group of people. Сommunication styles that are equally common in various situations of interpersonal interaction determine the personality orientation in communication. It has been established that self-presentation of adolescents is aimed at demonstrating personal achievements and the desire to make a favorable impression on a friend, class teacher (teacher), and classmates. When presenting themselves, adolescents with an authoritarian communication style use the «Desire to please» strategy; students with a manipulative communication style do not use the «Exemplary behavior» strategy; boys and girls with a dialogical orientation in communication have the «Tracking the impression made» strategy; schoolchildren who prefer the «Intimidation» strategy are focused primarily on the manipulative style of communication. The images of self-presentation identified in the work can serve as a basis for compiling training courses and educational programs on effective self-presentation in significant situations of interaction in the age group under study.
Keywords: личность; personality; подростковый возраст; самопрезентация; adolescence; самопредъявление; самоподача; направленность в общении; self-presentation; self-delivery; communication orientation